Holistic Wisdom from Abrahamic Faiths’ Earliest Encounters with Ancient China: Towards a Constructive Chinese Natural Theology - Feng, Jacob Chengwei (Religions, 2023)
Philosophies in the East and West have favored wisdom in their search for truths. The Chinese civilization has sought holistic wisdom in its long history of absorbing the Abrahamic faiths since the seventh century. This paper aims to investigate how the Abrahamic faiths have interacted with ancient Chinese culture. In particular, this paper will examine the earliest written records in Chinese of the Luminous Religion (or Jingjiao), the earliest Jews in Kaifeng, and the earliest Muslims in China. By analyzing their theology of creation with reference to the Holy Spirit and qi (wind/breath/pneuma), this paper attempts a constructive Chinese natural theology based on a sympathetic and critical assessment of Alister McGrath’s natural theology but makes up for his spirit deficit. This paper argues that the holistic wisdom achieved in the early integration process of the Abrahamic faiths with the Chinese culture is closely intertwined with the Spirit and qi, which provides a fruitful ground to construct a Chinese natural theology. The contribution of this paper lies in its original research into the earliest written records of the three Abrahamic faiths in China from the perspective of the doctrine of creation and its relationship with the Spirit and qi.